Dampak Konvergensi IFRS Terhadap Relevansi Nilai Informasi Akuntansi (Studi Konseptual) - Anida Fauzizah (AKUNTANSI 45, 2023)
A transparent accounting system is one of the mostimportant information especially for investors. International Financial Reporting Standards (IFRS) was introduced to increase quality and accuracy in financial reporting. The purpose of this study is to examine the effect of IFRS convergence in Indonesia on the quality of accounting. Value relevance is used to measure the quality of accounting information, where information that has high quality is information with a high level of relevance. In this study, the price model and return model as additionel tests are used to test value relevance testing. The result of this study indicate that, during the implementation of IFRS convergence in Indonesia, there was an increase in the relevance of accounting values.